Outcome of invasive pneumococcal disease: a UK based study. Issue 3 (1st September 2000) - Shackley, F; Knox, K; Morris, J Bowen; Crook, D; Griffiths, D; Mayon-White, R; George, R; Willocks, L; Moxon, ER
Abstract : METHODS: The records of 106 children aged less than 5 years with invasive disease caused by Streptococcus pneumoniae were reviewed. RESULTS: The clinical manifestations were meningitis (37%), upper respiratory tract infection (24%), pneumonia (19%), and occult bacteraemia (18%). One child died and seven had persisting neurological impairment. Five serotypes caused 83% of disease and 92% of the serotypes are included in the seven valent conjugate vaccines which are undergoing trials. CONCLUSIONS: These data suggest that S pneumoniae infection is associated with a low case fatality rate but substantial morbidity in the UK.